ChemInform Abstract: Broensted Acid‐Surfactant‐Combined Catalyst for the Mannich Reaction in Water. Issue 28 (15th July 2014) - Chang, Tao; He, Leqin; Bian, Li; Han, Haiyan; Yuan, Mingxia; Gao, Xiaorui
Abstract 3‐(N, N‐Dimethyloctylammonium) propanesulfonic acid tosylate, together with similar compounds, is synthesized and found to be a good and recyclable catalyst for the three‐component Mannich reaction.